Essays on Banking and Financial Regulations - Kravtsov, Oleg; Janda, Karel; Teplý, Petr, 1977-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This dissertation thesis comprises three working papers on the selected topics in financial regulations, supervision and financial stability. The focus is on the analysis of the response of financial institutions to the regulations and regulatory actions across the time and regions. The first essay examines the changes in the portfolio structures and investment decisions associated with EU-wide stress test rounds in 2011, 2014 and 2016. Using the empirical methods of causal inference and event study, we document a substantial impact of EU-wide stress tests in 2011, 2014 and 2016 on the banks’ portfolio strategies. We find that regulatory stress testing contributes to a decline of risk density of portfolios, which is mostly attributable to a decrease in its numerator i.e. risk-weighted assets. Seemingly it does not affect the realized risk that is measured by the proportion of non-performing exposure in portfolios. We argue that regulatory stress testing incentivizes banks to altering a mix of assets in their balance sheets towards less capital-intensive areas, potentially creating concerns on the concentrations and economic misallocation of resources. On the other hand, we observe that the enhanced regulatory scrutiny prevents the stress tested banks from engaging in risky behaviour i.e. increase risk in a portfolio or excessive loan growth. Thus, the regulatory stress testing fulfils its objective of promoting prudent risk management practices. Our results are robust in a number of alternative specifications such as modelling with instrument variable in the continuous form within the treated sample, under less restrictive assumptions of the structural equations and based on the alternative samples. In the second essay, we examine the impact of the supervision efforts as a monitoring activity and regulatory scrutiny on the risk-adjusted performance of the banking institutions in the Central Eastern Southern Eastern Europe.
Our main hypothesis is that the supervisory monitoring efforts are associated with lower riskiness of the banking institutions and simultaneously not impacting their performance. We find that a higher intensity of supervision activities, especially by the centralized form of supervision, contributes to the decline in riskiness of the larger banks while not affecting their economic performance. The regulatory power and stringency indicate a positive effect on the risk-adjusted performance for the capital constraint banks, but moderately decreasing the economic performance of the larger banks. The findings highlight the potential area of attention for regulators and policymakers and therefore, contributes to the designing of effective supervision mechanism in the region. The third essay with a corresponding article has been published in the European Financial and Accounting Journal (co-author Karel Janda). This paper investigates the implications and effectiveness of the microprudential policy on Basel III leverage ratio as an additional measure to already existing capital requirements for the banking sector in the Czech Republic and across the CEE region. We identify the potential binding constraints from the regulatory limits and analyse the interactions among ratios over the country’s economic cycle (from 2007 to 2016). Our analysis suggests that the total assets or exposure in contrast to the Tier 1 capital are the main contributors to the cyclical movements. The results of the regression model confirm that the leverage ratio in normal times is strongly pro-cyclical to the capital ratio and counter-cyclical in the crisis period. Our findings point to the active balance sheet adjustments in response to the cyclical changes and therefore advocate in favour of constraining regulations on the leverage.
Vedoucí práce: Karel Janda
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations